Targeting active RAS with molecular glue - Wenjing Su; Xuben Hou (Elsevier, 2024)
Activating mutations in RAS genes, notably KRASG12C, are pervasive in numerous cancers, presenting formidable challenges to therapy due to their elusive druggability. The landmark discovery of KRASG12C allosteric inhibitors marked a transformative milestone in cancer treatment, resulting in the approval of sotorasib and adagrasib. However, limitations in the depth and duration of response prompted the quest for alternative strategies. Recently, Holderfield et al., Wasko et al., and Jiang et al. reported on tri-complex inhibitors, namely RMC-7977 and RMC-6236, targeting activated RAS variants, demonstrating promising preclinical efficacy surpassing adagrasib. These advancments signify a paradigm shift in RAS oncology, promising enduring therapeutic benefits and warranting further clinical exploration.